Challenges faced by postgraduate French speaking students who are learning in English : a case study of Rwandan students in the School of Education at the University of the Witwatersrand. - Sibomana, Emmanuel (My University, 2010)
It is widely recognized that language plays a central role in learning (Evans and Green, 2007; Abasi and Graves, 2008). Rollnick (2000, p.95) argues that “language is the link between the learner and the teacher.” Stressing the importance of English as a medium of instruction, Hyland (2002, p.2) points out that “for college and university students in many countries, mastering English, and the right English, to succeed in learning their subjects through the medium of English in textbooks, lectures, study groups and so on is a matter of great urgency.” According to a number of scholars (Burke and Wyatt-Smith, 1996; Cummins, 1996; Cadman, 2000; Deem and Brehony, 2000 and Evans and Green, 2007) second language speakers of English are likely to experience difficulties in using this language in their studies, since it is a language that they have not yet fully mastered. One aim of this qualitative research project was to understand the challenges faced by a group of Rwandan French-speaking postgraduate students in the School of Education at the University of the Witwatersrand, who are now learning and researching in English. A second aim was to understand the strategies used by the students to address these challenges and a third aim was to investigate the degree and kind of institutional support offered to these students. Questionnaires were administered to 22 students and interviews were conducted with four students and three lecturers/supervisors. Artefacts such as assignment tasks and lecturers‟ feedback on assignments and research work also contributed to the data. Findings from the case study suggest that these postgraduate students‟ previous „ways with words‟ (Heath, 1983) differ from those of the institution in which they are now studying. The main difference is that their previous educational institutions adopted a predominantly “banking approach” to education, while the University of the Witwatersrand adopts mainly a “problem posing approach” (Freire, 1968). Moreover, the use of „academic English‟, which is a genre of English itself (Rollnick, 2000; Paxton, 2007), is a great challenge especially for those who did not use this language as a medium of instruction in their previous studies.